How We Can Speak to Nature: Insights from Dialogical Philosophy and the Bible - Pauly, Marc (Studia Philosophiae Christianae, 2025)
In our age of ecological crisis, religious traditions have been viewed as co-responsible for our ecological problem, in particular Christianity. This paper utilizes dialogical philosophy to suggest how Christianity can also be viewed as part of the solution. The paper starts by presenting the dialogical speech thinking of Ferdinand Ebner, Martin Buber and Eugen Rosenstock-Huessy, discussing their ideas about grammar, names and the power of language to create a relationship between speaker and hearer. Next, the paper goes on to show how according to these thinkers, nature is limited in its relational capabilities. Nonetheless, this paper then argues that the resources of dialogical philosophy can fruitfully be applied in renewing our human relations with nature, exploring what it can mean to speak to nature. Biblical passages are used to illustrate these ideas and to show that this dialogical approach to nature can be seen as consonant with the Christian tradition. ---------------------------------------- Zgłoszono: 19/06/2025. Zrecenzowano: 21/10/2025. Zaakceptowano do publikacji: 30/11/2025.